Modeling heavy metals uptake by plants: A case study of phytoremediation from southern Turkey - Şan, Tülay. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2018., 2019)
Removal of heavy metals from the soil by phytoremediation has been a subject of interest in recent years due to the difficulties of removing heavy metals with conventional methods. Modeling is considered as a promising tool to understand the mechanisms of contaminant uptake by plants since it is the cheapest and the most time efficient way to predict the removal efficiency of the contaminant from the soil.The aim of this thesis is to model the uptake of heavy metals (Cu, Pb, Zn) by Sorghum and Sunflower. The model data were obtained from soil in Kilis, which was planted in 2011 and 2012. Modeling of heavy metal uptake was conducted using the GoldSim contaminant transport module. This mass transport model is a mathematical representation of an actual system, which can be used to simulate and hence predict the fate and transport of heavy metals within a coupled environmental system comprising both soil and plant.Model results are in good agreement with observed data. Kd, partition coefficient heavy metals between soil water and soil solid values for Cu, Zn, and Pb are found to be 3.47, 3.05, and 2.42 respectively. Results suggest that the uptake rate of Sunflower was higher than that of Sorghum. Partition coefficient is found to be the most effective parameter, followed by transpiration rate and plant mass in determining the residue heavy metal soil concentration.
Keywords: Heavy metals -- Environmental aspects.; Heavy metals -- Environmental aspects -- Turkey.